Building community networks and engagement for effective TB case management - Augustine Kumah; Augustine Kumah (Frontiers in Public Health)
Tuberculosis (TB) remains a significant global public health challenge, particularly in low- and middle-income countries. Effective TB case management requires comprehensive strategies that extend beyond clinical treatment and involve community engagement and networks. This narrative review explores the role of community networks and engagement in enhancing TB case management, focusing on how communities contribute to improved detection, treatment adherence, and long-term management. Drawing on a wide range of studies, the review highlights the importance of participatory approaches, the use of community health workers (CHWs), and multi-sectoral collaboration in TB care. It emphasizes the role of culturally tailored interventions and the need for greater investment in building sustainable community networks. The discussion also explores the challenges and barriers to effective community engagement, such as stigma, lack of resources, and structural inequalities. The review concludes by proposing recommendations for future strategies to strengthen community networks and engagement, ensuring more comprehensive and effective TB case management.